Foramen Magnum Dural Arteriovenous Fistula Presenting With Thoracic Myelopathy: Technical Case Report With 2-Dimensional Operative Video. Issue 1 (7th April 2021) - Gadot, Ron; Gopakumar, Sricharan; Wagner, Kathryn; Xu, David S; Raper, Daniel M S; Burkhardt, Jan-Karl; Ropper, Alexander E
Abstract: BACKGROUND AND IMPORTANCE: Dural arteriovenous fistulas (dAVFs) are vascular abnormalities of the central nervous system that can cause a wide array of neurological dysfunction depending on their location, flow, and propensity to rupture. Symptomatic dAVFs at the cranio-cervical junction usually result in hemorrhage or cervical myelopathy. Distantly located dAVFs of the foramen magnum are a rare cause of thoracic intrinsic myelopathy. CLINICAL PRESENTATION: An 83-yr-old man presented with progressive lower extremity weakness, numbness, and difficulty walking along with episodes of bowel incontinence. Magnetic resonance imaging of the cervical spine demonstrated multilevel cervical disc disease with stenosis and longitudinal cervical cord signal change extending into the upper thoracic spinal cord. Cerebral and spinal angiography revealed a dAVF in the lateral foramen magnum region. Given the location, feeding vasculature, and morphology of the fistula, endovascular embolization was not attempted. Microsurgical resection with confirmative indocyanine green fluorescent imaging was performed with adequate obliteration of the fistula. The patient's neurological baseline was preserved postoperatively with improvement of lower extremity numbness. CONCLUSION: We present a brief overview of this neuropathologic entity and demonstrate microsurgical resection of a foramen magnum dAVF through operative video. Craniocervical dAVFs should remain on the differential diagnosis of patients presenting with progressive thoracolumbar myelopathy.